All optical detection of picosecond spin-wave dynamics in 2D annular antidot lattice. (12th January 2018) - Porwal, Nikita; Mondal, Sucheta; Choudhury, Samiran; De, Anulekha; Sinha, Jaivardhan; Barman, Anjan; Datta, Prasanta Kumar
Abstract: Novel magnetic structures with precisely controlled dimensions and shapes at the nanoscale have potential applications in spin logic, spintronics and other spin-based communication devices. We report the fabrication of 2D bi-structure magnonic crystal in the form of embedded nanodots in a periodic Ni80 Fe20 antidot lattice structure (annular antidot) by focused ion-beam lithography. The spin-wave spectra of the annular antidot sample, studied for the first time by a time-resolved magneto-optic Kerr effect microscopy show a remarkable variation with bias field, which is important for the above device applications. The optically induced spin-wave spectra show multiple modes in the frequency range 14.7 GHz–3.5 GHz due to collective interactions between the dots and antidots as well as the annular elements within the whole array. Numerical simulations qualitatively reproduce the experimental results, and simulated mode profiles reveal the spatial distribution of the spin-wave modes and internal magnetic fields responsible for these observations. It is observed that the internal field strength increases by about 200 Oe inside each dot embedded within the hole of annular antidot lattice as compared to pure antidot lattice and pure dot lattice. The stray field for the annular antidot lattice is found to be significant (0.8 kOe) as opposed to the negligible values of the same for the pure dot lattice and pure antidot lattice. Our findings open up new possibilities for development of novel artificial crystals.